Memaksimalkan Keuntungan Dalam Ekonomi Islam (As-Sahla: Journal Of Islamic Studies, 2025)
This study aims to analyze the concept of profit maximization from the perspective of Islamic economics by emphasizing its theological, ethical, and social orientations in contrast to conventional economic thought. The research employs a qualitative method with a library research approach, analyzing both classical and contemporary literature relevant to Islamic economic principles. The findings indicate that in Islamic economics, profit is not considered an ultimate goal but rather a means to achieve falah a holistic form of well-being that encompasses material, spiritual, and social dimensions. This concept places justice, honesty, and social responsibility as fundamental values within every economic activity. Maximum profit is only considered legitimate when it is obtained through lawful, fair, and beneficial mechanisms. Moreover, the principle of tawhid provides a spiritual dimension to economic practices, positioning them as acts of worship to Allah SWT. The study concludes that Islamic economic paradigms emphasize a balance between profit, ethics, and barakah (divine blessing), implying that the ultimate goal is not mere wealth accumulation but sustainable welfare and social justice.